A high wear-resistant environment-friendly type extruded insulation low-voltage power cable material

CN122978595APending Publication Date: 2026-10-27NANCHANG CABLE(NANNING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611369333.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0002]低压电力电缆是输配电系统的核心基础部件,广泛应用于建筑布线、工业制造、新能源场站、轨道交通等诸多领域,当前的低压电力电缆绝缘材料常用聚氯乙烯、交联聚乙烯、聚乙烯、聚丙烯或聚烯烃弹性体等树脂体系,其中的聚氯乙烯材料加工方便、成本较低,但燃烧时容易释放烟雾及含卤腐蚀性气体,不利于环保和人员疏散安全

Benefits of technology

本发明是在母粒制备阶段,以POE-G-MAH的柔性POE链段与聚烯烃基体的相容性,并利用马来酸酐基团与阻燃改性粒子、氨修饰分散填料以及聚多巴胺包覆PE粉表面的氨基、羟基或酚羟基发生反应或强相互作用,从而先把多种功能组分预先包覆、分散和连接起来,在后续双螺杆挤包时,过氧化二异丙苯分解产生少量自由基,使聚烯烃链段与聚硅氧烷中的乙烯基发生有限接枝或锚定反应,使得绝缘层内部形成聚烯烃连续相、POE-G-MAH相容桥、阻燃耐磨功能粒子复合的复合结构,进而减少界面孔隙和填料团聚,提高应力传递和能量耗散能力,使得材料在具有较高氧指数、较低烟密度、较低质量磨损和较低摩擦系数的同时,仍能够保持较高的拉伸强度、断裂伸长率和20℃体积电阻率,解决了传统低烟无卤电缆料中阻燃性、耐磨性、柔韧性和电绝缘稳定性难以兼顾的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of high wear-resistant environment-friendly type extrusion insulation low-voltage power cable materials, belong to cable material technical field, specifically including conductor and the insulating layer extruded on the outer periphery of conductor, insulating layer includes the following composition by weight parts: polypropylene 40-48 parts, low-density polyethylene 18-22 parts, ethylene-octene copolymer 26-28 parts, compatible flame-retardant wear-resistant masterbatch 75-85 parts, initiator 0.1-0.2 parts and additive 3 parts.The application is prepared by flame-retardant modified particle, ammonia modified dispersion filler, polydopamine coated PE powder and POE-G-MAH mixing, compatible flame-retardant wear-resistant masterbatch, and limited interface anchoring is carried out in subsequent extrusion process, while improving the flame-retardant, smoke suppression and wear resistance of material, the mechanical strength and insulation performance of material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable material technology, specifically to a high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material. Background Technology

[0002] Low-voltage power cables are the core basic components of power transmission and distribution systems, and are widely used in many fields such as building wiring, industrial manufacturing, new energy power stations, and rail transit. The insulation materials of current low-voltage power cables commonly use resin systems such as polyvinyl chloride, cross-linked polyethylene, polyethylene, polypropylene, or polyolefin elastomers. Among them, polyvinyl chloride is easy to process and has a low cost, but it is easy to release smoke and halogen-containing corrosive gases when burned, which is not conducive to environmental protection and personnel evacuation safety.

[0003] Currently, although low-smoke halogen-free polyolefin materials have advantages in terms of environmental protection and low smoke, they usually require the addition of high content of inorganic flame retardants such as magnesium hydroxide and aluminum hydroxide to achieve a good flame retardant effect. The addition of a large amount of inorganic flame retardants will significantly increase the viscosity of the system and easily cause problems such as filler agglomeration, poor interfacial bonding, and decreased processing fluidity, thereby reducing the tensile strength, elongation at break and electrical insulation stability of the material. To improve the wear resistance of low-smoke halogen-free cable materials, existing technologies often incorporate lubricating or wear-resistant components such as silicone oil, polyethylene wax, ultra-high molecular weight polyethylene powder, boron nitride, and boehmite. However, if these components are simply blended directly, they often suffer from poor compatibility, uneven dispersion, easy precipitation, or detachment during friction, resulting in unstable wear resistance and potentially weakening the material's flame retardancy, mechanical properties, and extrusion processing performance. Summary of the Invention

[0004] The purpose of this invention is to provide a high-wear-resistant and environmentally friendly extruded insulated low-voltage power cable material, which solves the technical problem that the flame retardant, low-smoke, wear-resistant and electrical insulation properties of existing low-smoke halogen-free cable materials need to be further improved.

[0005] The objective of this invention can be achieved through the following technical solution: a high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material, comprising a conductor and an insulation layer extruded around the conductor, wherein the insulation layer comprises the following components by weight: 40-48 parts polypropylene, 18-22 parts low-density polyethylene, 26-28 parts ethylene-octene copolymer, 75-85 parts compatible flame-retardant and wear-resistant masterbatch, 0.1-0.2 parts initiator, and 3 parts additives; The compatible flame-retardant and wear-resistant masterbatch is obtained by mixing flame-retardant modified particles, ammonia-modified dispersant filler, polydopamine-coated PE powder and POE-G-MAH through intensive mixing.

[0006] Furthermore, the weight ratio of the flame-retardant modified particles, ammonia-modified dispersant filler, polydopamine-coated PE powder, and POE-G-MAH is 25-28:12-16:28-33:50-55.

[0007] Furthermore, the preparation method of the compatible flame-retardant and wear-resistant masterbatch is as follows: flame-retardant modified particles, ammonia-modified dispersion filler, polydopamine-coated PE powder and POE-G-MAH are added to a mixer, the mixing temperature is set to 125-135℃, the mixer is mixed for 18-22 minutes, and the material is discharged to obtain the compatible flame-retardant and wear-resistant masterbatch.

[0008] Furthermore, the preparation method of flame-retardant modified particles is as follows: 2-aminoethylphosphonic acid, amino-terminated polymethylphenyl polysiloxane, γ-glycidyl etheroxypropyltrimethoxysilane and anhydrous ethanol are mixed, the reaction system is heated to 50-60℃ and kept at that temperature for 60-80 min, the reaction system is cooled to room temperature, an alkaline solution is added to the reaction system, and the mixture is stirred at room temperature for 20-30 min, boric acid and zinc phytate are added to the reaction system, the reaction system is heated to 70-80℃ and kept at that temperature for 50-60 min, magnesium hydroxide and aluminum hydroxide are added to the reaction system, and the mixture is stirred at that temperature for 160-180 min, followed by post-treatment to obtain flame-retardant modified particles.

[0009] Furthermore, the ratio of 2-aminoethylphosphonic acid, amino-terminated polymethylphenyl polysiloxane, γ-glycidyl etheroxypropyltrimethoxysilane, anhydrous ethanol, alkali solution, boric acid, zinc phytate, magnesium hydroxide, and aluminum hydroxide is 3.8-4.2g:8-9g:6-7g:100mL:10mL:0.8-1g:1.3-1.7g:15-17g:21-23g, and the alkali solution is a 0.5-0.8mol / L sodium hydroxide aqueous solution. The post-treatment includes: after the reaction is completed, the reaction system is subjected to negative pressure, and low-boiling substances are removed by vacuum evaporation to obtain flame-retardant modified particles.

[0010] Furthermore, the preparation method of amino-terminated polymethylphenyl polysiloxane is as follows: octamethylcyclotetrasiloxane, diphenyldiethoxysilane, diethoxymethylvinylsilane and sulfuric acid are mixed and stirred, the reaction system is heated to 85-95℃ and kept at this temperature for 50-70 min, 1,3-bis(aminopropyl)tetramethyldisiloxane is added to the reaction system, and the reaction is kept at this temperature for 2-3 h. After post-treatment, amino-terminated polymethylphenyl polysiloxane is obtained.

[0011] Furthermore, the weight ratio of octamethylcyclotetrasiloxane, diphenyldiethoxysilane, diethoxymethylvinylsilane, sulfuric acid, and 1,3-bis(aminopropyl)tetramethyldisiloxane is 28-30:10-12:3-4:0.1-0.5:10-11, and the mass fraction of the sulfuric acid is 80-85%. The post-treatment includes: after the reaction is complete, adding anhydrous sodium carbonate to the reaction system to adjust the pH of the system to 7, then adding purified water to the reaction system, stirring and dispersing for 20-30 minutes, allowing it to stand and separate the liquids, washing the upper oil phase three times with purified water, and then transferring it to a rotary evaporator with a water bath temperature of 80-90℃ to remove low-boiling substances under reduced pressure to obtain amino-terminated polymethylphenyl polysiloxane.

[0012] Furthermore, the preparation method of the ammonia-modified dispersion filler is as follows: hexagonal boron nitride, plate-like boehmite, aminopropyltriethoxysilane, dodecyltriethoxysilane, anhydrous ethanol and deionized water are mixed and stirred, the reaction system is heated to 55-65℃, sodium hydroxide aqueous solution is added to the reaction system, the reaction is kept at the temperature for 2-3 hours, and then post-processed to obtain the ammonia-modified dispersion filler.

[0013] Furthermore, the ratio of hexagonal boron nitride, plate-like boehmite, aminopropyltriethoxysilane, dodecyltriethoxysilane, anhydrous ethanol, deionized water, and sodium hydroxide aqueous solution is 60-70g:40-50g:4-5g:1.8-2g:800mL:80mL:10-15mL, and the concentration of the sodium hydroxide aqueous solution is 0.5-0.8mol / L. The post-treatment includes: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the filter cake is washed three times with deionized water, and then transferred to a drying oven at a temperature of 70-80℃ and dried to constant weight to obtain the ammonia-modified dispersion packing.

[0014] Furthermore, the preparation method of polydopamine-coated PE powder is as follows: ultra-high molecular weight polyethylene micro powder and Tris-HCl buffer are mixed and ultrasonically dispersed for 40-50 min. Dopamine hydrochloride is added to the reaction system, and the mixture is stirred and reacted at room temperature for 6-8 h. After post-treatment, polydopamine-coated PE powder is obtained.

[0015] Furthermore, the ratio of ultra-high molecular weight polyethylene micro powder, Tris-HCl buffer, and dopamine hydrochloride is 10g:500mL:2-3g, the concentration of Tris-HCl buffer is 0.1mol / L, and the pH is 8.5. The post-processing includes: after the reaction is complete, filtration is performed, the filter cake is washed with purified water until neutral, and then dried. The filter cake is transferred to a drying oven at a temperature of 70-80℃ and dried to constant weight to obtain polydopamine-coated PE powder.

[0016] Furthermore, a preparation process for a high-wear-resistant and environmentally friendly extruded insulated low-voltage power cable material is proposed. Specifically, polypropylene, low-density polyethylene, ethylene-octene copolymer, compatible flame-retardant and wear-resistant masterbatch, initiator and additives are mixed and added to a twin-screw extruder, melt-mixed for 28-32s, extruded and coated on the outside of the conductor, and after water cooling, an insulation layer with a thickness of 0.8±0.05mm is formed on the outside of the conductor, thus obtaining the high-wear-resistant and environmentally friendly extruded insulated low-voltage power cable material.

[0017] Furthermore, the weight ratio of the polypropylene, low-density polyethylene, ethylene-octene copolymer, compatible flame-retardant and wear-resistant masterbatch, initiator, and additives is 40-48:18-22:26-28:75-85:0.1-0.2:3. The initiator is dicumyl peroxide. The auxiliary additives consist of antioxidant 1010, antioxidant 168, ethylene bis-stearamide, and β-crystalline polypropylene nucleating agent in a weight ratio of 5:3:4:1. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 145℃, Zone 2 150℃, Zone 3 155℃, Zone 4 165℃, Zone 5 175℃, Zone 6 180℃, Zone 7 180℃, and Zone 8 185℃. The extruder head temperature is 180-185℃, the die temperature is 185-192℃, and the screw speed is 180-220 r / min.

[0018] The present invention has the following beneficial effects: This invention utilizes the compatibility of flexible POE segments (POE-G-MAH) with the polyolefin matrix during the masterbatch preparation stage. It leverages the reaction or strong interaction between maleic anhydride groups and flame-retardant modified particles, ammonia-modified dispersing fillers, and the amino, hydroxyl, or phenolic hydroxyl groups on the surface of polydopamine-coated PE powder to pre-encapsulate, disperse, and connect multiple functional components. During subsequent twin-screw extrusion, the decomposition of dicumyl peroxide generates a small amount of free radicals, causing limited grafting or anchoring reactions between the polyolefin segments and the vinyl groups in the polysiloxane. This process enables the formation of a composite structure within the insulation layer, consisting of a continuous polyolefin phase, POE-G-MAH compatibility bridges, and flame-retardant and wear-resistant functional particles. This reduces interfacial porosity and filler agglomeration, improving stress transmission and energy dissipation capabilities. As a result, the material maintains high tensile strength, elongation at break, and volume resistivity at 20°C while exhibiting high oxygen index, low smoke density, low mass wear, and low coefficient of friction. This solves the problem of balancing flame retardancy, wear resistance, flexibility, and electrical insulation stability in traditional low-smoke halogen-free cable materials.

[0019] This invention also involves the ring-opening, condensation, and siloxane rearrangement reactions of octamethylcyclotetrasiloxane, diphenyldiethoxysilane, and diethoxymethylvinylsilane under acidic conditions to form polymethylphenyl polysiloxane containing phenyl, vinyl, and amino terminal groups; then, the polymethylphenyl polysiloxane undergoes epoxy ring-opening, hydrolytic condensation, hydrogen bonding, acid-base, or coordination reactions with 2-aminoethylphosphonic acid, γ-glycidoxypropyltrimethoxysilane, boric acid, zinc phytate, magnesium hydroxide, and aluminum hydroxide, resulting in the formation of polymethylphenyl polysiloxane containing phenyl, vinyl, and amino terminal groups. A composite modified layer containing silicon, phosphorus, boron, and zinc is formed, giving the resulting flame-retardant modified particles an organosilicon compatible interface and a multi-element flame-retardant interface. This reduces the agglomeration of flame retardants in the polyolefin matrix, reduces the adverse effects of fillers on tensile strength, elongation at break, and volume resistivity, and during combustion, magnesium hydroxide and aluminum hydroxide absorb heat and release water, phosphorus and zinc promote char formation, boron forms a glassy shielding layer, and silicon forms a silicon-containing residual structure, thereby increasing the oxygen index and reducing smoke density, so that the material exhibits good low-smoke, halogen-free, environmentally friendly flame-retardant effects.

[0020] This invention also employs aminopropyltriethoxysilane and dodecyltriethoxysilane to surface-treat hexagonal boron nitride and lamellar boehmite, resulting in filler surfaces possessing both amino active sites and long-chain hydrophobic structures. The amino sites can undergo ring-opening reactions or form strong polar interactions with the maleic anhydride groups in POE-G-MAH, while the long-chain hydrophobic structures improve the wetting and dispersion effects of the lamellar filler in polyolefin melts. Furthermore, after ultra-high molecular weight polyethylene micropowder is coated with dopamine through self-polymerization, a polydopamine layer containing catechol, amino, and imine structures is formed on its surface, enabling… Originally inert PE micropowder can form a stronger interfacial bond with compatibilizers, flame retardant particles and flake fillers. In the material, hexagonal boron nitride provides lamellar slip friction reduction, flake boehmite provides anti-scratch and anti-ploughing support, and ultra-high molecular weight polyethylene micropowder provides self-lubrication and anti-wear properties. The polydopamine layer and silane modified layer can prevent these wear-resistant components from falling off from the matrix during friction, thereby reducing mass wear and friction coefficient while avoiding secondary abrasive wear caused by filler debonding and particle peeling, so that the insulation layer can obtain more stable long-term wear resistance. Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] In this invention, magnesium hydroxide is a commercially available product with an effective ingredient content of 99% and a particle size of 200-800 nm; In this invention, aluminum hydroxide is a commercially available product with an effective ingredient content of 99% and a particle size of 1.0-2.0 μm; In this invention, hexagonal boron nitride is a commercially available product with an effective ingredient content of 98%, has a sheet-like structure, a sheet diameter of 2-5 μm, and a thickness of 0.05-0.3 μm; In this invention, the platy boehmite is a commercially available product with an effective ingredient content of 98%, a platy diameter of 1-3 μm, and a thickness of 0.1-0.15 μm; In this invention, the ultra-high molecular weight polyethylene micro powder is a commercially available product, processed at the extrusion grade, with an average molecular weight of 3 million to 9 million and a particle size of 8 to 20 μm; In this invention, the polypropylene is a commercially available product, with a processing grade of injection molding and a grade of GH-25D; In this invention, the low-density polyethylene is a commercially available product, with a processing grade of injection molding and a model number of 2426H; In this invention, the ethylene-octene copolymer is a commercially available product, with a processing grade of injection molding and a grade of C0560D; In this invention, POE-G-MAH is a commercially available product, with a processing grade of injection molding and a grade of GR-209.

[0023] Preparation Example 1 This preparation example provides a preparation process for a compatible flame-retardant and wear-resistant masterbatch, specifically including the following steps: Step 1: Prepare amino-terminated polymethylphenyl polysiloxane. Weigh out 280g of octamethylcyclotetrasiloxane, 100g of diphenyldiethoxysilane, 30g of diethoxymethylvinylsilane, and 1g of 80% sulfuric acid and add them to a reaction flask. Stir the mixture and heat it to 85℃. Keep the mixture at this temperature for 50 min. Add 100g of 1,3-bis(aminopropyl)tetramethyldisiloxane to the reaction flask and keep the mixture at this temperature for 2 h. Add anhydrous sodium carbonate to the reaction flask to adjust the pH of the system to 7. Then add 1L of purified water to the reaction flask and stir to disperse the mixture for 20 min. Allow the mixture to stand and separate the layers. Wash the upper oil phase three times with purified water and transfer it to a rotary evaporator with a water bath temperature of 80℃. Apply a negative pressure to -0.09MPa and remove low-boiling substances by vacuum evaporation to obtain amino-terminated polymethylphenyl polysiloxane.

[0024] In the reaction, octamethylcyclotetrasiloxane undergoes a ring-opening reaction under sulfuric acid catalysis. Diphenyldiethoxysilane and diethoxymethylvinylsilane participate in condensation and siloxane rearrangement, simultaneously introducing methyl, phenyl, and vinyl structures into the siloxane backbone. 1,3-Di(aminopropyl)tetramethyldisiloxane serves as the amino end-capping agent, yielding polymethylphenyl polysiloxanes with amino, phenyl, and vinyl groups. Amino-terminated polymethylphenyl polysiloxanes possess flexible siloxane backbones, improving the material's flexibility and friction reduction. The phenyl groups on the siloxane backbone contribute to improved thermal stability and carbonization residue, while the vinyl groups can participate in free radical anchoring during subsequent extrusion. The amino groups provide active sites for subsequent reactions, thereby increasing the material's tensile strength, elongation at break, and oxygen index, and reducing the coefficient of friction and mass wear.

[0025] Step 2: Preparation of flame-retardant modified particles Weigh out 38g of 2-aminoethylphosphonic acid, 80g of amino-terminated polymethylphenyl polysiloxane, 60g of γ-glycidyl etheroxypropyltrimethoxysilane, and 1L of anhydrous ethanol and add them to a reaction flask. Stir the mixture and heat it to 50℃. Maintain the temperature for 60min. Cool the reaction flask to room temperature and add 100mL of 0.5mol / L sodium hydroxide aqueous solution. Stir the mixture at room temperature for 20min. Add 8g of boric acid and 13g of zinc phytate to the reaction flask. Heat the mixture to 70℃ and maintain the temperature for 50min. Add 150g of magnesium hydroxide and 210g of aluminum hydroxide to the reaction flask. Stir the mixture and maintain the temperature for 160min. Apply a negative pressure to the reaction flask to -0.09MPa and remove low-boiling-point substances by vacuum distillation to obtain flame-retardant modified particles.

[0026] In the reaction, the amino groups on 2-aminoethylphosphonic acid and amino-terminated polymethylphenyl polysiloxane molecules undergo ring-opening bonding with epoxy groups, forming an organosilicon-phosphorus structure containing hydroxyl, amino, phosphonic acid, and siloxane segments. Subsequently, an aqueous sodium hydroxide solution is added, causing the trimethoxysilane to hydrolyze to generate silanol, which further undergoes condensation. The addition of boric acid and zinc phytate then leads to the formation of hydrogen bonds, acid-base interactions, and zinc ion coordination. Finally, the addition of magnesium hydroxide and aluminum hydroxide causes the silanol, phosphonic acid, zinc phytate, and boric acid structures formed by hydrolysis to adsorb or bind to the surfaces of magnesium hydroxide and aluminum hydroxide, forming a composite modified layer containing silicon, phosphorus, boron, and zinc. The treated flame-retardant particles have a composite particle with an organosilicon compatible layer and a multi-element flame-retardant layer on their surface, making them easier to disperse in polyolefins, less prone to agglomeration, and less likely to form interfacial pores, thereby reducing the loss of tensile strength, elongation at break, and volume resistivity. During combustion, magnesium hydroxide and aluminum hydroxide absorb heat and release water, phosphorus and zinc promote char formation, boron forms a glassy protective layer, and silicon forms a silicon-containing residual structure, which increases the oxygen index while reducing smoke density.

[0027] Step 3: Preparation of ammonia-modified dispersion filler Weigh out 60g of hexagonal boron nitride, 40g of plate-like boehmite, 4g of aminopropyltriethoxysilane, 1.8g of dodecyltriethoxysilane, 800mL of anhydrous ethanol and 80mL of deionized water, add them to a reaction flask and stir. Heat the reaction system to 55℃, add 10mL of 0.5mol / L sodium hydroxide aqueous solution to the reaction system, keep the reaction at this temperature for 2h, cool the reaction flask to room temperature, filter, wash the filter cake three times with deionized water and transfer it to a drying oven at 70℃, dry it to constant weight, and obtain the ammonia-modified dispersion filler.

[0028] In the reaction, aminopropyltriethoxysilane and dodecyltriethoxysilane first hydrolyze under alkaline conditions to generate silanols, which then condense with hydroxyl groups or edge active sites on the filler surface, forming amino and long-chain alkyl modifications on the filler surface. The amino groups can undergo ring-opening reactions or strong polar bonding with the maleic anhydride groups in POE-G-MAH, while the long-chain alkyl groups improve the wettability between the filler and the polyolefin melt. Hexagonal boron nitride itself has lamellar slip properties, which can reduce the coefficient of friction; lamellar boehmite can provide anti-scraping, anti-ploughing, and support functions. After silane treatment, these lamellar fillers are more easily and uniformly spread in the matrix and are less likely to detach during friction, thus significantly reducing mass wear and the coefficient of friction, while maintaining good mechanical properties and electrical insulation stability.

[0029] Step 4: Prepare polydopamine-coated PE powder Weigh out 100g of ultra-high molecular weight polyethylene micro powder and 5000mL of Tris-HCl buffer solution with a concentration of 0.1mol / L and pH=8.5. Add the mixture to a reaction flask and sonicate for 40min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. Add 20g of dopamine hydrochloride to the reaction flask and stir at room temperature for 6h. Filter the mixture and wash the filter cake with purified water until neutral. Dry the filter cake and transfer it to a drying oven at 70℃ to dry to constant weight to obtain polydopamine-coated PE powder.

[0030] In the reaction, ultra-high molecular weight polyethylene (UHMWPE) micropowder is first fully dispersed in a Tris-HCl buffer solution at pH 8.5, and then dopamine hydrochloride is added. After self-polymerization and condensation, a polydopamine coating layer is formed. After polydopamine coating, the surface of the UHMWPE micropowder has active structures such as catechol, amino groups, and imines, which can form stronger interfacial interactions with POE-G-MAH, flame-retardant modified particles, and ammonia-modified dispersing fillers. This retains the self-lubricating and anti-wear effects of polydopamine-coated PE powder while reducing secondary abrasive wear caused by particle shedding.

[0031] Step 5: Prepare compatible flame-retardant and wear-resistant masterbatch Weigh out the following by weight: 25 parts of flame-retardant modified particles, 12 parts of ammonia-modified dispersant filler, 28 parts of polydopamine-coated PE powder, and 50 parts of POE-G-MAH. Add them to a mixer, set the mixing temperature to 125℃, mix for 18 minutes, and discharge to obtain a compatible flame-retardant and wear-resistant masterbatch.

[0032] In the reaction, flame-retardant modified particles, ammonia-modified dispersant filler, polydopamine-coated PE powder, and POE-G-MAH are intensively mixed. The POE segments in POE-G-MAH have good compatibility with polyolefin resins, and the maleic anhydride groups can react or strongly interact with amino, hydroxyl, phenolic hydroxyl, and silanol groups. After intensive mixing, the functional components are uniformly dispersed in the masterbatch, thus preventing large particle agglomeration, interfacial voids, and phase debinding when polypropylene, low-density polyethylene, and ethylene-octene copolymers are subsequently added and extruded. The material forms a composite structure in which the continuous polyolefin phase, POE-G-MAH compatibility bridge, and flame-retardant and wear-resistant functional particles are combined. This results in good tensile strength, elongation at break, and volume resistivity at 20°C even with a high filler content, while also achieving a high oxygen index, low smoke density, low mass wear, and low coefficient of friction.

[0033] Preparation Example 2 This preparation example provides a preparation process for a compatible flame-retardant and wear-resistant masterbatch, specifically including the following steps: Step 1: Prepare amino-terminated polymethylphenyl polysiloxane. Weigh out 290g of octamethylcyclotetrasiloxane, 110g of diphenyldiethoxysilane, 35g of diethoxymethylvinylsilane, and 3g of 83% sulfuric acid and add them to a reaction flask. Stir the mixture and heat it to 90℃. Keep the mixture at this temperature for 60min. Add 105g of 1,3-bis(aminopropyl)tetramethyldisiloxane to the reaction flask and keep the mixture at this temperature for 2.5h. Add anhydrous sodium carbonate to the reaction flask to adjust the pH of the system to 7. Then add 1L of purified water to the reaction flask and stir to disperse for 25min. Let the mixture stand and separate the layers. Wash the upper oil phase three times with purified water and transfer it to a rotary evaporator with a water bath temperature of 85℃. Apply a negative pressure to -0.09MPa and remove low-boiling substances by vacuum evaporation to obtain amino-terminated polymethylphenyl polysiloxane.

[0034] Step 2: Preparation of flame-retardant modified particles Weigh out 40g of 2-aminoethylphosphonic acid, 85g of amino-terminated polymethylphenyl polysiloxane, 65g of γ-glycidyl etheroxypropyltrimethoxysilane, and 1L of anhydrous ethanol and add them to a reaction flask. Stir the mixture and heat it to 55℃. Maintain the temperature for 70min. Cool the reaction flask to room temperature and add 100mL of 0.65mol / L sodium hydroxide aqueous solution. Stir the mixture at room temperature for 25min. Add 9g of boric acid and 15g of zinc phytate to the reaction flask. Heat the mixture to 75℃ and maintain the temperature for 55min. Add 160g of magnesium hydroxide and 220g of aluminum hydroxide to the reaction flask. Stir the mixture and maintain the temperature for 170min. Apply a negative pressure to the reaction flask to -0.09MPa and remove low-boiling-point substances by vacuum distillation to obtain flame-retardant modified particles.

[0035] Step 3: Preparation of ammonia-modified dispersion filler Weigh out 65g of hexagonal boron nitride, 45g of plate-like boehmite, 4.5g of aminopropyltriethoxysilane, 1.9g of dodecyltriethoxysilane, 800mL of anhydrous ethanol, and 80mL of deionized water, and add them to a reaction flask. Stir the mixture and heat the reaction system to 60℃. Add 13mL of 0.65mol / L sodium hydroxide aqueous solution to the reaction system and keep the reaction at this temperature for 2.5h. Cool the reaction flask to room temperature, filter the mixture, wash the filter cake three times with deionized water, and then transfer it to a drying oven at 75℃. Dry the cake to constant weight to obtain the ammonia-modified dispersion filler.

[0036] Step 4: Prepare polydopamine-coated PE powder Weigh out 100g of ultra-high molecular weight polyethylene micro powder and 5000mL of Tris-HCl buffer solution with a concentration of 0.1mol / L and pH=8.5. Add the mixture to a reaction flask and sonicate for 45min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. Add 25g of dopamine hydrochloride to the reaction flask and stir at room temperature for 7h. Filter the mixture and wash the filter cake with purified water until neutral. Dry the filter cake and transfer it to a drying oven at 75℃ to dry to constant weight to obtain polydopamine-coated PE powder.

[0037] Step 5: Prepare compatible flame-retardant and wear-resistant masterbatch Weigh out the following by weight: 26.5 parts of flame-retardant modified particles, 14 parts of ammonia-modified dispersion filler, 30 parts of polydopamine-coated PE powder, and 53 parts of POE-G-MAH. Add them to a mixer, set the mixing temperature to 130℃, mix for 20 minutes, and then discharge to obtain a compatible flame-retardant and wear-resistant masterbatch.

[0038] Preparation Example 3 This preparation example provides a preparation process for a compatible flame-retardant and wear-resistant masterbatch, specifically including the following steps: Step 1: Prepare amino-terminated polymethylphenyl polysiloxane. Weigh out 300g of octamethylcyclotetrasiloxane, 120g of diphenyldiethoxysilane, 40g of diethoxymethylvinylsilane, and 5g of 85% sulfuric acid and add them to a reaction flask. Stir the mixture and heat it to 95℃. Keep the temperature for 70 min. Add 110g of 1,3-bis(aminopropyl)tetramethyldisiloxane to the reaction flask and keep the temperature for 3 h. Add anhydrous sodium carbonate to the reaction flask to adjust the pH of the system to 7. Then add 1L of purified water to the reaction flask and stir to disperse for 30 min. Let the mixture stand and separate the layers. Wash the upper oil phase three times with purified water and transfer it to a rotary evaporator with a water bath temperature of 90℃. Remove the low-boiling substances by vacuum evaporation to obtain amino-terminated polymethylphenyl polysiloxane.

[0039] Step 2: Preparation of flame-retardant modified particles Weigh out 42g of 2-aminoethylphosphonic acid, 90g of amino-terminated polymethylphenyl polysiloxane, 70g of γ-glycidyl etheroxypropyltrimethoxysilane, and 1L of anhydrous ethanol and add them to a reaction flask. Stir the mixture and heat it to 60℃. Maintain the temperature for 80min. Cool the reaction flask to room temperature and add 100mL of 0.8mol / L sodium hydroxide aqueous solution. Stir the mixture at room temperature for 30min. Add 10g of boric acid and 17g of zinc phytate to the reaction flask. Heat the mixture to 80℃ and maintain the temperature for 60min. Add 170g of magnesium hydroxide and 230g of aluminum hydroxide to the reaction flask. Stir the mixture and maintain the temperature for 180min. Apply a negative pressure to the reaction flask to -0.09MPa and remove low-boiling-point substances by vacuum distillation to obtain flame-retardant modified particles.

[0040] Step 3: Preparation of ammonia-modified dispersion filler Weigh out 70g of hexagonal boron nitride, 50g of plate-like boehmite, 5g of aminopropyltriethoxysilane, 2g of dodecyltriethoxysilane, 800mL of anhydrous ethanol and 80mL of deionized water, add them to a reaction flask and stir. Heat the reaction system to 65℃, add 15mL of 0.8mol / L sodium hydroxide aqueous solution to the reaction system, keep the reaction at this temperature for 3h, cool the reaction flask to room temperature, filter, wash the filter cake three times with deionized water and transfer it to a drying oven at 80℃, dry it to constant weight, and obtain the ammonia-modified dispersion filler.

[0041] Step 4: Prepare polydopamine-coated PE powder Weigh out 100g of ultra-high molecular weight polyethylene micro powder and 5000mL of Tris-HCl buffer solution with a concentration of 0.1mol / L and pH=8.5. Add the mixture to a reaction flask and sonicate for 50min. Fix the reaction flask on an iron stand with a mechanical stirrer and stir. Add 30g of dopamine hydrochloride to the reaction flask and stir at room temperature for 8h. Filter the mixture and wash the filter cake with purified water until neutral. Dry the filter cake and transfer it to a drying oven at 80℃ to dry to constant weight to obtain polydopamine-coated PE powder.

[0042] Step 5: Prepare compatible flame-retardant and wear-resistant masterbatch Weigh out the following by weight: 28 parts of flame-retardant modified particles, 16 parts of ammonia-modified dispersant filler, 33 parts of polydopamine-coated PE powder, and 55 parts of POE-G-MAH. Add them to a mixer, set the mixing temperature to 135℃, mix for 22 minutes, and then discharge to obtain a compatible flame-retardant and wear-resistant masterbatch.

[0043] Example 1 This embodiment provides a manufacturing process for a high-wear-resistant, environmentally friendly extruded insulated low-voltage power cable material, specifically as follows: Antioxidant 1010, antioxidant 168, ethylene bis-stearamide, and β-crystalline polypropylene nucleating agent were mixed evenly in a weight ratio of 5:3:4:1 to obtain auxiliary additives. Weigh out the following components by weight: 40 parts polypropylene, 18 parts low-density polyethylene, 26 parts ethylene-octene copolymer, 75 parts of the compatible flame-retardant and wear-resistant masterbatch prepared in Preparation Example 1, 0.1 parts dicumyl peroxide, and 3 parts additives. Add these components to a twin-screw extruder. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 145℃, Zone 2 150℃, Zone 3 155℃, Zone 4 165℃, Zone 5 175℃, Zone 6 180℃, Zone 7 180℃, and Zone 8 185℃. The extruder head temperature is 180℃, and the die temperature is 185℃. The screw speed is 180 r / min, and the melt mixing is carried out for 28 seconds. The material is then extruded and coated onto the outside of the conductor. After water cooling, an insulation layer with a thickness of 0.8 ± 0.05 mm is formed on the outside of the conductor, resulting in a high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material. The conductor is a copper wire with a cross-sectional area of ​​10 ± 0.1 mm².

[0044] Example 2 This embodiment provides a manufacturing process for a high-wear-resistant, environmentally friendly extruded insulated low-voltage power cable material, specifically as follows: Antioxidant 1010, antioxidant 168, ethylene bis-stearamide, and β-crystalline polypropylene nucleating agent were mixed evenly in a weight ratio of 5:3:4:1 to obtain auxiliary additives. Weigh out the following components by weight: 44 parts polypropylene, 20 parts low-density polyethylene, 27 parts ethylene-octene copolymer, 80 parts of the compatible flame-retardant and wear-resistant masterbatch prepared in Preparation Example 2, 0.15 parts dicumyl peroxide, and 3 parts additives. Add these components to a twin-screw extruder. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 145℃, Zone 2 150℃, Zone 3 155℃, Zone 4 165℃, Zone 5 175℃, Zone 6 180℃, Zone 7 180℃, and Zone 8 185℃. The extruder head temperature is 183℃, and the die temperature is 188℃. The screw speed is 200 r / min, and the melt mixing is carried out for 30 s. The material is then extruded and coated onto the outside of the conductor. After water cooling, an insulation layer with a thickness of 0.8 ± 0.05 mm is formed on the outside of the conductor, resulting in a high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material. The conductor is a copper wire with a cross-sectional area of ​​10 ± 0.1 mm².

[0045] Example 3 This embodiment provides a manufacturing process for a high-wear-resistant, environmentally friendly extruded insulated low-voltage power cable material, specifically as follows: Antioxidant 1010, antioxidant 168, ethylene bis-stearamide, and β-crystalline polypropylene nucleating agent were mixed evenly in a weight ratio of 5:3:4:1 to obtain auxiliary additives. Weigh out the following components by weight: 48 parts polypropylene, 22 parts low-density polyethylene, 28 parts ethylene-octene copolymer, 85 parts of the compatible flame-retardant and wear-resistant masterbatch prepared in Preparation Example 3, 0.2 parts dicumyl peroxide, and 3 parts additives. Add these components to a twin-screw extruder. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 145℃, Zone 2 150℃, Zone 3 155℃, Zone 4 165℃, Zone 5 175℃, Zone 6 180℃, Zone 7 180℃, and Zone 8 185℃. The extruder head temperature is 185℃, and the die temperature is 192℃. The screw speed is 220 r / min, and the melt mixing is carried out for 28-32 seconds. The material is then extruded and coated onto the outside of the conductor. After water cooling, an insulation layer with a thickness of 0.8 ± 0.05 mm is formed on the outside of the conductor, resulting in a high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material. The conductor is a copper wire with a cross-sectional area of ​​10 ± 0.1 mm².

[0046] Comparative Example 1 The difference between this comparative example and Example 3 is that, in the preparation of the compatible flame retardant and wear-resistant masterbatch, step 1 was omitted, and amino-terminated polymethylphenyl polysiloxane was not added in step 2.

[0047] Comparative Example 2 The difference between this comparative example and Example 3 is that, in the preparation of the compatible flame-retardant and wear-resistant masterbatch, a mixture of magnesium hydroxide and aluminum hydroxide in a ratio of 17g:23g is used to replace the flame-retardant modified particles in step 5 in equal amounts.

[0048] Comparative Example 3 The difference between this comparative example and Example 3 is that, in the preparation of the compatible flame-retardant and wear-resistant masterbatch, aminopropyltriethoxysilane and dodecyltriethoxysilane were not added in step 3.

[0049] Comparative Example 4 The difference between this comparative example and Example 3 is that, in the preparation of the compatible flame-retardant and wear-resistant masterbatch, step 4 is omitted, and the ultra-high molecular weight polyethylene micro powder in step 4 is used instead of the polydopamine-coated PE powder in step 5.

[0050] Comparative Example 5 The difference between this comparative example and Example 3 is that, in the preparation of the compatible flame-retardant and wear-resistant masterbatch, the internal mixing was omitted in step 5, and POE-G-MAH was not added.

[0051] Performance testing: The tensile strength, elongation at break, volume resistivity at 20°C, oxygen index, and smoke density of the insulation layer of the high wear-resistant and environmentally friendly extruded insulated low-voltage power cable materials prepared in Examples 1-3 and Comparative Examples 1-5 were determined in accordance with the standard GB / T 32129-2015 "Halogen-free Low-smoke Flame-retardant Cable Materials for Wires and Cables". The mass wear and coefficient of friction of the high wear-resistant and environmentally friendly extruded insulated low-voltage power cable materials prepared in Examples 1-3 and Comparative Examples 1-5 were determined in accordance with the standard GB / T 3960-2016 "Plastics Sliding Friction and Wear Test Method". The above performance test data consists of at least 5 sets, and then the arithmetic mean is taken. The specific test data is shown in Table 1 below.

[0052] Table 1 - Performance Test Data of Samples Data Analysis: Comparative analysis of the data in Table 1 above shows that the tensile strength of the insulation layer of the high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material prepared in Example 3 of this invention reaches 18.3 MPa, the volume resistivity at 20℃ reaches 4.5 × 10¹³ Ω·m, the oxygen index reaches 36.1%, the smoke density is reduced to 10¹ m²·kg⁻¹, the mass wear is reduced to 0.008 g, and the coefficient of friction reaches 0.15. Comparative analysis of the data from Examples 1-3 shows that with the increase in the amount of compatible flame-retardant and wear-resistant masterbatch and the content of modified components, the tensile strength increased from 16.4 MPa to 18.3 MPa, the volume resistivity at 20°C increased from 2.6 × 10¹³ Ω·m to 4.5 × 10¹³ Ω·m, the oxygen index increased from 34.1% to 36.1%, and the smoke density increased from 128 m²·kg⁻¹. - ¹ Reduced to 101 m²·kg -¹, mass wear decreased from 0.013g to 0.008g, and the coefficient of friction decreased from 0.19 to 0.15.

[0053] Comparative Example 1 eliminated the amino-terminated polymethylphenyl polysiloxane, resulting in an increase in the coefficient of friction from 0.15 in Example 3 to 0.28, an increase in mass wear from 0.008 g to 0.021 g, a decrease in the oxygen index from 36.1% to 33.6%, and an increase in smoke density from 101 m²·kg⁻¹. - ¹Increased to 136 m²·kg - ¹. This indicates that polymethylphenyl polysiloxane not only reduces surface energy and improves friction and wear resistance, but also participates in the formation of silicon-containing residual layers and improves its anchoring and compatibility in polyolefin systems through active structures such as vinyl and amino groups.

[0054] Comparative Example 2, where unmodified magnesium hydroxide / aluminum hydroxide replaced the flame-retardant modified particles, showed a decrease in tensile strength to 13.8 MPa, elongation at break to 236%, volume resistivity at 20°C to 1.3 × 10¹³ Ω·m, oxygen index to 31.8%, and smoke density to 176 m²·kg⁻¹. - ¹. This indicates that although simply adding magnesium hydroxide and aluminum hydroxide still provides some flame retardant effect, the lack of a silicon, phosphorus, boron, and zinc composite modification layer results in poor dispersion and weak interfacial bonding of the flame retardant particles in polyolefins, making them prone to agglomeration and porosity defects. Consequently, this simultaneously impairs mechanical properties, electrical insulation properties, and low-smoke flame retardant properties.

[0055] Comparative Example 3, which was not treated with aminosilanes and long-chain silanes on hexagonal boron nitride and platy boehmite, still had an oxygen index of 34.7% and a smoke density of 122 m²·kg⁻¹. - ¹ indicates that the main flame-retardant system still exists; however, its mass wear increased to 0.024 g, the coefficient of friction increased to 0.30, and the tensile strength and elongation at break decreased to 15.4 MPa and 262%, respectively. This indicates that surface treatment of hexagonal boron nitride and boehmite improved their uniform dispersion in the polyolefin matrix, and the ammonia-modified dispersant significantly contributed to wear resistance, friction reduction, mechanical retention, and electrical insulation stability.

[0056] Comparative Example 4, after replacing polydopamine-coated PE powder with uncoated ultra-high molecular weight polyethylene micropowder, showed an oxygen index of 35.1% and a smoke density of 114 m²·kg⁻¹. -¹ The flame retardant performance did not decrease significantly, but the mass wear increased from 0.008g in Example 3 to 0.022g, the coefficient of friction increased from 0.15 to 0.27, and the elongation at break decreased from 337% to 276%. This indicates that although ultra-high molecular weight polyethylene micropowder itself has a self-lubricating effect, its surface inertness is strong when it is not coated with polydopamine. The bonding between it and POE-G-MAH, flame retardant particles, and flake fillers is lower than that of polydopamine-coated PE powder, making it easy to detach during friction and causing secondary abrasive wear.

[0057] Comparative Example 5, without internal mixing and the addition of POE-G-MAH, exhibited a tensile strength of only 12.5 MPa, an elongation at break of only 178%, a volume resistivity at 20°C decreasing to 7.5 × 10¹² Ω·m, a wear rate increasing to 0.038 g, and a coefficient of friction increasing to 0.39. This indicates that without the flexible compatibility bridge and maleic anhydride reaction sites of POE-G-MAH, flame-retardant particles, flake fillers, and PE powder are difficult to effectively encapsulate, connect, and disperse, ultimately leading to interfacial porosity, filler agglomeration, and interphase debonding, resulting in a simultaneous decline in mechanical properties, electrical insulation properties, and wear resistance.

[0058] This invention describes the preparation of a compatible flame-retardant and wear-resistant masterbatch through the compounding of flame-retardant modified particles, ammonia-modified dispersant fillers, polydopamine-coated PE powder, and POE-G-MAH. POE-G-MAH is used to pre-coat, connect, and disperse these particles, and a small amount of dicumyl peroxide is used during the extrusion process for limited interfacial anchoring, forming a continuous resin phase, a compatible bridge, and an insulating layer in which functional particles work together. This improves the material's flame retardancy, smoke suppression, and wear resistance while also enhancing its mechanical strength and insulation properties.

[0059] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-wear-resistant and environmentally friendly extruded insulated low-voltage power cable material, comprising a conductor and an insulation layer extruded around the conductor, characterized in that, The insulation layer comprises the following components by weight: 40-48 parts polypropylene, 18-22 parts low-density polyethylene, 26-28 parts ethylene-octene copolymer, 75-85 parts compatible flame-retardant and abrasion-resistant masterbatch, 0.1-0.2 parts initiator, and 3 parts additives. The compatible flame-retardant and wear-resistant masterbatch is obtained by mixing flame-retardant modified particles, ammonia-modified dispersant filler, polydopamine-coated PE powder and POE-G-MAH through intensive mixing.

2. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 1, characterized in that, The weight ratio of the flame-retardant modified particles, ammonia-modified dispersant filler, polydopamine-coated PE powder, and POE-G-MAH is 25-28:12-16:28-33:50-55.

3. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 1, characterized in that, The method for preparing flame-retardant modified particles is as follows: 2-aminoethylphosphonic acid, amino-terminated polymethylphenyl polysiloxane, γ-glycidyl etheroxypropyltrimethoxysilane and anhydrous ethanol are mixed. The reaction system is heated to 50-60℃ and kept at that temperature for 60-80 min. The reaction system is then cooled to room temperature. Alkali solution is added to the reaction system and stirred at room temperature for 20-30 min. Boric acid and zinc phytate are added to the reaction system. The reaction system is heated to 70-80℃ and kept at that temperature for 50-60 min. Magnesium hydroxide and aluminum hydroxide are added to the reaction system and stirred at that temperature for 160-180 min. After post-treatment, flame-retardant modified particles are obtained.

4. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 3, characterized in that, The ratio of 2-aminoethylphosphonic acid, amino-terminated polymethylphenyl polysiloxane, γ-glycidyl etheroxypropyltrimethoxysilane, anhydrous ethanol, alkali solution, boric acid, zinc phytate, magnesium hydroxide, and aluminum hydroxide is 3.8-4.2g:8-9g:6-7g:100mL:10mL:0.8-1g:1.3-1.7g:15-17g:21-23g. The post-treatment includes: after the reaction is completed, the reaction system is subjected to negative pressure, and low-boiling substances are removed by vacuum evaporation to obtain flame-retardant modified particles.

5. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 1, characterized in that, The preparation method of ammonia-modified dispersion filler is as follows: hexagonal boron nitride, plate boehmite, aminopropyltriethoxysilane, dodecyltriethoxysilane, anhydrous ethanol and deionized water are mixed and stirred, the reaction system is heated to 55-65℃, sodium hydroxide aqueous solution is added to the reaction system, the reaction is kept at the temperature for 2-3 hours, and then post-processed to obtain ammonia-modified dispersion filler.

6. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 5, characterized in that, The ratio of hexagonal boron nitride, platy boehmite, aminopropyltriethoxysilane, dodecyltriethoxysilane, anhydrous ethanol, deionized water, and sodium hydroxide aqueous solution is 60-70g:40-50g:4-5g:1.8-2g:800mL:80mL:10-15mL, and the concentration of the sodium hydroxide aqueous solution is 0.5-0.8mol / L. The post-treatment includes: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the filter cake is washed three times with deionized water, and then transferred to a drying oven at 70-80℃ and dried to constant weight to obtain the ammonia-modified dispersion packing.

7. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 1, characterized in that, The preparation method of polydopamine-coated PE powder is as follows: ultra-high molecular weight polyethylene micro powder and Tris-HCl buffer are mixed and ultrasonically dispersed for 40-50 min. Dopamine hydrochloride is added to the reaction system and stirred at room temperature for 6-8 h. After post-treatment, polydopamine-coated PE powder is obtained.

8. The high wear-resistant and environmentally friendly extruded insulated low-voltage power cable material according to claim 7, characterized in that, The ratio of ultra-high molecular weight polyethylene micro powder, Tris-HCl buffer, and dopamine hydrochloride is 10g:500mL:2-3g. The concentration of the Tris-HCl buffer is 0.1mol / L and the pH is 8.

5. The post-processing includes: after the reaction is complete, the mixture is filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 70-80℃ and dried to constant weight to obtain polydopamine-coated PE powder.